MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN BUDAYA ALAM MINANGKABAU MENGGUNAKAN MEDIA AUDIO VISUAL DI KELAS VIII-5 SMP NEGERI 18 PADANG - YUSMAINI, Drs. Suib Awrus, M.Pd, Yofita Sandra, S.Pd., M.Pd (Serupa The Journal of Art Education, 2014)
This study aims to determine the improvement of student learning outcomes Alam Minangkabau culture of subjects in class VIII-5 Junior High School 18 Champaign totaling 34 people by using audio-visual media. Data collected using the research instruments and observation sheets. To see the changes in students' learning activities within two cycles of cycles I and II. Data were obtained and analyzed using percentages. The research findings indicate that student learning outcomes improved significantly, it can be seen from the average prasiklus 77.6 to 66.65 in the first cycle. In the second cycle is also increased by an average of 86. It can be concluded that the audio-visual media can improve student learning outcomes Alam Minangkabau culture of subjects in class VIII-5 Junior High School 18 Padang.Key words: Media Audio Visual, Peningkatan Hasil Belajar. Pelajaran Budaya Alam Minangkabau di kelas VIII-5 SMP Negeri 18 Padang